41.9k views
2 votes
Simplify. can someone help i am lost

Simplify. can someone help i am lost-example-1

1 Answer

5 votes

9514 1404 393

Answer:


(S)\cdot(H)\cdot(E)\cdot(e)\cdot(\theta)\cdot(\epsilon+1+1)\cdot(\xi)\cdot(s)\cdot(h)

Explanation:

The inverse function of fun(x) is indicated using a -1 exponent. That is ...


\text{fun}(\text{fun}^(-1)(x)) = x\\\text{fun}^(-1)(\text{fun}(x)) = x

The usual trig identities apply:

sin²(x) +cos²(x) = 1

sec²(x) -tan²(x) = 1

sin(x) = 1/csc(x)

__

So, the expression simplifies to ...


(S)\cdot(H)\cdot(E)\cdot(e)\cdot(\theta)\cdot(\epsilon+1+1)\cdot(\xi)\cdot(s)\cdot(h)

User Webvision
by
5.6k points